The Effect of Sorghum (Sorghum Bicolor (L.)) Snack Bar Formulation on Organoleptic Properties - Henricus Yayan Setyanto (JURNAL PENDIDIKAN DAN KELUARGA, 2022)
The snack bar is one of many potential functional products. The common ingredients used are cereals and beans, but information on the usage of formulation ratios for each ingredient and cooking method is still needed. Sorghum is a potential cereal as an ingredient because of its high fiber content and is able to become the basic ingredient for snack bars, instead of oats. In this study, the snack bar formulation used sorghum concentrations sequences 12, 18, and 24% w/w and 2 cooking methods, namely hot process and cold process. In general, the organoleptic results showed that there was no significant difference in each formulation, but there were significant in the cooking method, the hot process also had a higher value than the cold process-snack bar in terms of taste, color, texture, and aroma.